2017
DOI: 10.1016/j.kjms.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of barbed suture in minimally invasive radical prostatectomy: A systematic review and meta‐analysis

Abstract: As one of the earliest surgeries applying knotless barbed suture, the minimally invasive radical prostatectomy (MIRP) was reported to have various effects on the patients and the surgeons. This study reviewed the available evidence about the efficacy and safety of barbed sutures in MIRP. We searched ClinicalTrials.gov, Cochrane Register of Clinical Studies, PubMed, and Embase to identify randomized controlled trials (RCTs) and cohort studies addressing the application of barbed sutures and conventional sutures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
2
12
2
3
Order By: Relevance
“…In addition to a reduction in operative time at gynecological surgeries, there are emerging data on other benefits and their successful application to minimally invasive urological and gastrointestinal surgeries. [15][16][17][18][19] The results of cosmesis after dermal closure with barbed sutures during cesarean were documented as non-inferior to the conventional sutures in the one trial that was included. 12 Comparable cosmetic outcomes have been documented with their use for dermal closure in benign gynecological surgeries; however, the patient satisfaction rate with the use of barbed sutures was significantly higher than with staples (70.12 ± 20.93 vs 50.56 ± 17.46, P < .001).…”
Section: Countrymentioning
confidence: 99%
“…In addition to a reduction in operative time at gynecological surgeries, there are emerging data on other benefits and their successful application to minimally invasive urological and gastrointestinal surgeries. [15][16][17][18][19] The results of cosmesis after dermal closure with barbed sutures during cesarean were documented as non-inferior to the conventional sutures in the one trial that was included. 12 Comparable cosmetic outcomes have been documented with their use for dermal closure in benign gynecological surgeries; however, the patient satisfaction rate with the use of barbed sutures was significantly higher than with staples (70.12 ± 20.93 vs 50.56 ± 17.46, P < .001).…”
Section: Countrymentioning
confidence: 99%
“…After further docking of Da Vinci Xi ® Surgical System, a distal ileal segment is mobilized to reach down the urethral stump. Using a 35 or 45 cm bidirectional barbed suture 3/0 (Filbloc ® Assut, Europe) as a first step we stitch the Denonvilliers Fascia (DF) with both needles, as performed during urethro-vesical anastomosis of radical prostatectomy (RP) (21)(22)(23). Using the left needles, the DF is gently transposed to the fibrous part of the sphincter with to bites from left to right.…”
Section: Anastomosis Technique and Totally Intracorporeal Neobladder Reconstructionmentioning
confidence: 99%
“…Initiated in 1964 [9], this approach has been first reported in gynaecological and plastic surgery previously [10]. And then some systematic reviews, in terms of radical prostatectomy [1113], have confirmed equivalence of biocompatibility and tensile strength of knotless barbed suture compared to conventional sutures in urological field [14, 15].…”
Section: Introductionmentioning
confidence: 99%